2008
DOI: 10.1111/j.1743-6109.2007.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Function Evaluation of the Tension-Free Vaginal Tape (TVT) and Transobturator Suburethral Tape (TOT) Incontinence Surgery: Results of a Prospective Study

Abstract: Introduction Significantly more women reporting stress urinary incontinence (SUI) or low urinary tract symptoms complained of sexual dysfunction than a general healthy female population. The use of a tension-free vaginal tape (TVT), placed transvaginally under the mid-urethra, ensures to reacquire continence but could affect sexual function. Aim This study aimed to determine if a suburethral tape for the correction of SUI cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 33 publications
(40 reference statements)
2
59
1
1
Order By: Relevance
“…There was significant improvement in sexual functions in FSFI total scores and all domains. Pace and Vicentini [22], in a similar study in 71 women showed 90.1% improvement in the FSFI scores at the postoperative 12 months in 71 women after TOT. Bekker et al [23] suggested that there was 21.3% improvement in sexual functions after urinary incontinence surgery.…”
Section: Discussionmentioning
confidence: 95%
“…There was significant improvement in sexual functions in FSFI total scores and all domains. Pace and Vicentini [22], in a similar study in 71 women showed 90.1% improvement in the FSFI scores at the postoperative 12 months in 71 women after TOT. Bekker et al [23] suggested that there was 21.3% improvement in sexual functions after urinary incontinence surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Thereafter, many studies were performed in which validated questionnaires were used during preoperative and postoperative periods and sexually active women were included. In these studies, sexual functions were reported as improved, unchanged or worsened after SUI surgery (11)(12)(13)(14). The aim of this study is to evaluate the effects of Transobturator tape (TOT) and Burch colposuspension procedures performed for urodynamic stress urinary incontinence on the quality of life and sexual functions of women.…”
mentioning
confidence: 99%
“…These results are in agreement with others. 11,25,27,28 Twenty-two patients (10 in the SUI group and 12 in the POP group) who were sexually active preoperatively did not regain sexual intercourse, because they worried that sexual activity would affect the surgical outcome. This is considered to be another negative effect on FSF after anterior vaginal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have investigated the potential impact of surgical procedures for SUI and POP on women's sexual health. Several authors have documented improvements, [11][12][13] as well as declines in FSF, 2,14 whereas other authors have suggested that such procedures have no impact. 15,16 The primary objective of the present study is to compare FSF and HRQOL, before and after anterior vaginal wall surgery for SUI and POP.…”
Section: Introductionmentioning
confidence: 99%